2001
DOI: 10.1303/aez.2001.471
|View full text |Cite
|
Sign up to set email alerts
|

Sex pheromone of the rice leaffolder moth, Cnaphalocrocis medinalis (Lepidoptera: Crambidae): Synthetic Indian and Philippine blends are not attractive to male C. medinalis, but are attractive to C. pilosa in the South-Western islands in Japan.

Abstract: Field bioassays with 3 different types of synthetic pheromone blends (Japanese, Indian and Philippine blends) based on geographic variation in the sex pheromones in Cnaphalocrocis medinalis were performed in 1998 and 1999 in the SouthWestern Islands of Japan. Only the Japanese blend attracted C. medinalis males, while neither the Indian nor the Philippine blend showed attractiveness, as in the Japan mainland. However, both the Philippine and the Indian blends attracted males of a different species, C. pilosa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…In such a case, male moths responding to the Philippine blend would appear in Japan. But, until now, no significant attraction of C. medinalis males by the Philippine blend has been recorded in Japan (e.g., Kawazu et al, 2001), suggesting no migration routes of C. medinalis to Japan from the Philippines. In the report regarding the identification of the Philippine blend, no behavioral activity has been demonstrated; only EAG activity was reported (Ramachandran et al, 1990).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In such a case, male moths responding to the Philippine blend would appear in Japan. But, until now, no significant attraction of C. medinalis males by the Philippine blend has been recorded in Japan (e.g., Kawazu et al, 2001), suggesting no migration routes of C. medinalis to Japan from the Philippines. In the report regarding the identification of the Philippine blend, no behavioral activity has been demonstrated; only EAG activity was reported (Ramachandran et al, 1990).…”
Section: Introductionmentioning
confidence: 94%
“…On the contrary, a blend of a Japanese population consists of different components, (Z)-11-octadecenal (Z11-18:Ald), (Z)-13-octadecenal (Z13-18:Ald), (Z)-11-octadecen-1-ol (Z11-18:OH) and (Z)-13-octadecen-1-ol (Z13-18:OH) at a ratio of 11 : 100 : 24 : 36 (Kawazu et al, 2000). Field tests in Japan using the above three synthetic blends have shown that only the Japanese blend had significant attractiveness to male C. medinalis (Kawazu et al, 2000(Kawazu et al, , 2001(Kawazu et al, , 2002. Also, in field tests at Hangzhou in the lower Yangzhe Valley, China, with the same three blends, only the Japanese blend was significantly attractive (Kawazu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The emission of sexual pheromones of female moths can be detected by males at relatively long distances of between 250 and 1100 m (Sharov et al, 2002;White et al, 2003); and identification by male depends on chemical composition, environmental conditions and the concentrations in which the pheromones are emitted (Linn and Roelofs, 1989;Kawazu et al, 2001;Sharov et al, 2002;Botero-Garcés e Isaacs, 2004;Takanashi et al, 2006;Larraín et al, 2007). In the bioassays with the 4-arms olfactometer, males reacted more positively and with greater intensity to the stimulus of the odour of the females alone than to the source of odours of plants plus females or the odour of plants alone.…”
Section: Figure 2 Preference Of Eurysacca Melanocampta Adults In a Ymentioning
confidence: 99%
“…Subsequent studies conducted in China and Vietnam found that the pheromone blend effective on leaffolder moths in the Philippines and India was ineffective in China, and the Japanese blend was only moderately effective (Kawazu et al. , , , ), suggesting a large geographical variation of pheromone communication within this species.…”
Section: Introductionmentioning
confidence: 96%
“…The two aldehydes were necessary for trap capture and the alcohols had synergistic effects; however, the two acetates were not attractive. Subsequent studies conducted in China and Vietnam found that the pheromone blend effective on leaffolder moths in the Philippines and India was ineffective in China, and the Japanese blend was only moderately effective (Kawazu et al 2001(Kawazu et al , 2004(Kawazu et al , 2005, suggesting a large geographical variation of pheromone communication within this species.…”
Section: Introductionmentioning
confidence: 97%